A shoshonitic dyke in Lohja, southern Finland - Lehtinen, Marek (fi=Turun yliopisto|en=University of Turku|, 2017)
The Lohja dyke is located about 25 km NW of the town of Lohja. It is E-W-trending, 5-6 m in width and sharply cross-cuts the Svecofennian bedrock, showing a chilled margin. The rock contains small xenoliths and carbonate-filled amygdales. Because of the proximity to the Lohja diabase swarm, the dyke required further studying. This included the single-grain U-Pb zircon dating using the LA-SC-ICPMS, the whole rock geochemistry with the ICPMS, and optical microscopy from thin sections. The standard heavy mineral separation resulted in only a few zircons. The zircons were rounded, colourless with a brownish tint and showed some igneous zoning. They yielded an age of 1.82 Ga, which indicates that they are all inherited. Additional ages of 1.78 Ga and 1.68 Ga suggest that the zircons had been heterogeneously affected by some later geological event. The geochemistry was compared to postorogenic dykes in southern Finland and Russian Karelia. The dyke is shoshonitic and more enriched in F, Rb, Ba and LREE than the rapakivi-related diabases, but less enriched than the lamprophyres. The closest analogue is the Åva lamprophyres with partially overlapping characteristics. Based on mineralogy and texture, the Lohja dyke is a diabase. The exact crystallisation age remains uncertain, but based on field observations and U-Pb ages, the dyke is younger than the 1.83–1.79 Ga metamorphic phases in the West Uusimaa Complex. The geochemistry indicates that the evolved melt derived from an enriched mantle, and that the Lohja dyke represents its own type of mafic magmatism.